Disegnare linee nel paesaggio - Emanuela, Morelli (Scuole di dottorato, 2005)
The subject of this study is the design of major road infrastructures, usually motorways or dual carriageways, as borderline cases in the controversial dichotomy between landscape and infrastructure. It retraces around a century of constructions and theories from the perspective of landscape, which is conceived in the broadest possible sense of system, and in all its cultural, ecological and perceptive aspects. The aim is to identify a method, or more precisely a basic design philosophy, that can guide the transformations in terms of quality. The infrastructure is thus no longer in opposition to the landscape, but rather an integral part of it.